Prehistoric predators - Switek, Brian; Csotonyi, Julius, 1973- (Kennebunkport, Maine : Applesauce Press, 2015)
"Discover the most dangerous carnivores that ever roamed the Earth in this exciting and action-packed exploration of Prehistoric Predators, featuring a unique cover that feels like dinosaur-skin!" --
Permian period -- Triassic period -- Jurassic period -- Cretaceous period -- Cenezoic era.
Includes index.
Keywords: Dinosaurs -- Juvenile literature; Carnivorous animals, Fossil -- Juvenile literature; Dinosaurs; Carnivorous animals, Fossil; Carnivorous animals, Fossil; Dinosaurs; Children's nonfiction; Juvenile works